Selective serotonin reuptake inhibitors and spermatogenesis - M. N. Korshunov; E. S. Korshunova; Yu. V. Kastrikin; S. P. Darenkov (Вестник урологии)
Introduction. According to the WHO data, depression is a common disease among women and men of reproductive age. One line of the correction of depressive disorders is selective serotonin reuptake inhibitors (SSRIs). The ingestions have shown that using SSRIs harms sperm quality. The literature date of evaluation of male fertility after discontinuation of antidepressants is quite limited.Purpose of the study. To evaluate the influence of Fluoxetine intake on semen parameters, sperm DNA fragmentation and hormonal status.Materials and methods. Twenty-five men (mean age - 35.2 ± 4.5 yo) with depression were included in the study. Fluoxetine (20 mg per day) was prescribed to all the patients for 12 wk. Semen parameters, sperm DNA fragmentation, sex hormones levels were measured before-after treatment and 3 mo behind discontinuation.Results. After 12 weeks of the treatment the mean semen volume decreased from 3.1 ± 0.7 to 2.9 ± 0.7 ml (p = 0.638), sperm concentration - from 39.4 ± 18.5 to 34.3 ± 16.8 mln/ml (p = 0.384), sperm motility decreased from 41.7 ± 7.6 to 35.5 ± 7.8% (p < 0.05), the mean percent of normal morphology form - from с 12.7 ± 2.8 to 10.7 ± 2.2% (p < 0.001). Sperm DNA fragmentation increased 16.2 ± 4.9 to 22.2 ± 4.3% (p < 0.001). The mean semen volume, sperm concentration, motility, percentage of normal morphology increased and reverted to the normal levels after 3 mounts of drug discontinuation. Sperm DNA fragmentation index decreased, and it had the values less than before the treatment that positively correlated with the reduction of depression's symptoms. It was not significant dynamics in hormonal parameters before and after the therapy.Conclusion. Using fluoxetine has a reversible negative effect on male fertility. It is important to inform the patients about the temporary side effects of SSRIs in fatherhood planning cases.